A severe right-to-left intracardiac shunt after NobleStitch failure: when a device is needed. Issue 5 (23rd August 2020) - Trabattoni, Daniela; Gili, Sebastiano; Teruzzi, Giovanni; Tamborini, Gloria
Abstract: Background: Transcatheter closure of patent foramen ovale (PFO) has been demonstrated to be superior to medical therapy in stroke prevention in selected patients. Beyond traditional permanent metallic devices, NobleStitch EL, a suture-based system, has been developed as a potential alternative. Case summary: A 50-year-old man underwent transcatheter closure of PFO with mild interatrial septal bulging and tunnel-like morphology with a NobleStitch device. A transthoracic echocardiography performed immediately after PFO closure showed residual shunt (RS), which persisted unchanged at staged controls, due to the inability of the delivery system to capture both the septum primum and the septum secundum. A second procedure was performed with the implantation of a Figulla Flex II 27/30 mm device, with no RS detectable at control echocardiography. Discussion: The NobleStitch device is interesting in its concept, but several pitfalls may be encountered during its deployment. Opposite to permanent metallic devices, RSs after the procedure are not expected to decrease over time and should be managed with a different approach.